The marriage buyout : the troubled trajectory of U.S. alimony law - Starnes, Cynthia (Families, law, and society series., 2014)
From divorce court to popular culture, alimony is a dirty word. Unpopular and rarely ordered, the awards are frequently inconsistent and unpredictable. The institution itself is often viewed as an historical relic that harkens back to a gendered past in which women lacked the economic independence to free themselves from economic support by their spouses. In short, critics of alimony claim it has no place in contemporary visions of marriage as a partnership of equals. But as Cynthia Lee Starnes argues in The Marriage Buyout, alimony is often the only practical tool for ensuring that divorce.